Application of Viral Inhibitor Protein (VIP) Solution on the Survival Rate and Immunity of whiteleg shrimp (Litopenaeus vannamei) against white spot syndrome virus (WSSV) - Hendriana, Andri; Pratiwi, Salsabila Kusumaning; Fuadi , Muhammad; Sari , Sifa Fauziah Ganda; Mulya, Muhammad Arif; Iskandar, Andri (Universitas Djuanda, 2024)
Farmers frequently face a collapse in white-leg shrimp (Litopenaeus vannamei) production due to disease infection. White spot disease, which was spread by the white spot syndrome virus (WSSV) in Indonesia, is one of the disease outbreaks. Extensive research has been done, including providing immunostimulants to prevent the WSSV outbreak. The application of recombinant viral inhibitor protein (VIP solution) developed by Aquaculture Technology and Development PT Suri Tani Pemuka, Purwakarta, is an innovation to prevent the WSSV outbreak. This study aims to evaluate the administration of VIP solutions to avoid the WSSV outbreak. The treatment consists of control feed (PBS without VIP solution supplementation) and feeds supplemented by VIP solution at 2 mL kg-1 and 5 mL kg-1. The feeding trial used post-larvae shrimp stage 25 (PL25). All the treated shrimp were challenged with WSSV, while positive control shrimp were not given VIP solution feed and were challenged with WSSV. The parameters observed included survival rate (SR), phenoloxidase activity (PO), lysozyme activity, and water quality (temperature, pH, and DO). The results showed that the shrimp-fed VIP solution experienced a significant increase in SR and immune response in the challenge test with WSSV (p <0.05). Supplementing 2 mL kg-1 VIP solution showed higher phenoloxidase activity (p <0.05) and increased SR by 82.50 ± 2.29%. The administration of 2 mL kg-1 VIP Solution for whiteleg shrimp can improve the survival rate and immunity after being challenged with WSSV.